Macrophages as central mediators of sympathetic neuro-immune interplay in autoimmunity - Muntjewerff, Elke M.; Josyula, Vijay S.; Lehmair, Franziska; Christoffersson, Gustaf (Frontiers in Immunology, 2025)
The immune and nervous systems share common signaling mediators that enable neuroimmune communication, particularly at barrier tissues such as the gut, skin, and lungs. Emerging evidence implicates disturbances in this neuroimmune crosstalk—especially between sympathetic nerves and macrophages—in the pathogenesis of autoimmune diseases. This review highlights the role of sympathetic nerve–macrophage communication in maintaining tissue homeostasis and how its disruption contributes to autoimmune inflammation. Loss of sympathetic innervation, altered catecholamine levels, and imbalance between sympathetic and sensory nerves have been observed in rheumatoid arthritis, type 1 diabetes, sarcoidosis, inflammatory bowel disease, and alopecia areata. Mechanistically, macrophages interact with sympathetic neurons via β2-adrenergic receptor signaling or may act as norepinephrine sinks, modulating local inflammatory responses. Reduced norepinephrine availability and impaired adrenergic signaling correlate with increased cytokine production and tissue damage. Restoring neuroimmune communication through β-adrenergic modulation, macrophage-targeted therapies, or neuromodulation devices shows promise in preclinical and early clinical studies. We propose that targeting sympathetic neuro-immune interactions offers a novel, personalized therapeutic avenue for autoimmune disorders, emphasizing the need for deeper mechanistic understanding of nerve–macrophage dynamics across disease contexts.